Five new species of Caddisflies (Trichoptera: Insecta) from Upper Tenasserim Range, Thailand and Myanmar - Laudee, Pongsak; Malicky, Hans (Zootaxa, 2018)
Five new species of caddisflies are described from the Upper Tenasserim Range, including Chimarra keawpradubi n. sp., Ecnomus niyomwasi n. sp., Psychomyia pinsuwanae n. sp., Leptocerus suwannarati n. sp., and Setodes lertpongsombatae n. sp., based on distinctive characters of male genitalia. Chimarra keawpradubi n. sp. differs from other Chimarra spp. in ventral aspect of inferior appendages, each of which is rectangular with a bulging process apicoventrally and with an acute apex. The basal part of each inferior appendage is square and the apical part is narrow in E. niyomwasi n. sp., differentiating it from other species in the genus. Psychomyia pinsuwanae n. sp. differs from P. amphiaraos Malicky and Chantaramongkol 1997, a closely similar species, by characters of the inferior appendages; the inner branch of each inferior appendage has a long, straight spine on its inner side. Leptocerus suwannarati n. sp. can be distinguished from other Leptocerus spp. by the processes of segment X, which are long, thin, and symmetrical. Setodes lertpongsombatae differs from other Setodes spp. in characters of segment X, which is deeply divided subapically into two very long saber-like blades in lateral view.